2017
DOI: 10.1093/annonc/mdx196
|View full text |Cite
|
Sign up to set email alerts
|

Professional burnout in European young oncologists: results of the European Society for Medical Oncology (ESMO) Young Oncologists Committee Burnout Survey

Abstract: This is the largest burnout survey in European Young Oncologists. Burnout is common amongst YOs and rates vary across Europe. Achieving a good work/life balance, access to support services and adequate vacation time may reduce burnout levels. Raising awareness, support and interventional research are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
3
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 18 publications
7
86
3
11
Order By: Relevance
“…Moller and colleagues found that the more a person is motivated at work, the better their occupational health . An ESMO survey supported that good work/life balance and adequate vacation time contribute to reducing burnout levels. Our study also noted that a poor relationship with colleagues and an imbalance between work and family may lead to a high risk of burnout.…”
Section: Discussioncontrasting
confidence: 46%
“…Moller and colleagues found that the more a person is motivated at work, the better their occupational health . An ESMO survey supported that good work/life balance and adequate vacation time contribute to reducing burnout levels. Our study also noted that a poor relationship with colleagues and an imbalance between work and family may lead to a high risk of burnout.…”
Section: Discussioncontrasting
confidence: 46%
“…Therefore, it is difficult to view these findings with confidence. While there is concern regarding the reliability of the findings in Alacacioglu et al, (), Elit et al, (), and Glasberg et al, (), the studies from Banerjee et al () and Shanafelt, Gradishar, Kosty, Satele, et al, used a large sample of participants and were conducted across multiple European countries and the United States. This suggests that it is reasonable to conclude that being in a relationship with a significant other may help to protect individuals from burnout.…”
Section: Resultsmentioning
confidence: 99%
“…However, the moderate quality rating of Probst et al () and lack of statistical information from Elit et al, () suggests further replication of the findings are needed to assist generalisability. Seven of the studies (Banerjee et al, ; Blanchard et al, ; Cubero et al, ; Leung & Rioseco, ; Ramey et al, ; Roth et al, ; Shanafelt, Gradishar, Kosty, Satele, et al, ) found hours worked/excessive workload, delivery demands, a lack of free time, amount of clinical time or inadequate work‐life balance were associated with higher levels of burnout. These seven studies have quality ratings ranging from moderate to high (four as high), four had large sample sizes of N = >400, and data covers, North and South America, Europe, and Australasia, which gives confidence in the generalisability of the findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of burnout and compassion fatigue are increasing among healthcare professionals (HCPs) in the US and other developed countries (Banerjee et al, ; Gomez‐Urquiza et al, ; Shanafelt et al, ; Wu, Singh‐Carlson, Odell, Reynolds, & Su, ). Burnout and compassion fatigue directly affect the health of the clinician and research shows that clinician well‐being has a direct impact on patient health outcomes (Salyers et al, ).…”
Section: Introductionmentioning
confidence: 99%